Effective evaluation strategies in catholic religious education: A case study in schools in indonesia - Bawa Toron, Vinsen (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
Research examines the evaluation of learning in Catholic religious education. Learning evaluation is an important tool for improving the quality of Catholic religious education. This study aims to evaluate the role of religious teachers and parents in guiding students' moral formation. The research method uses a qualitative approach with a phenomenological tradition. Data is collected through interviews at Catholic schools in Indonesia, as well as semi-structured interviews with six senior and junior Catholic religion teachers. Data analysis is carried out by applying Creswell's steps with the help of the ATLAS ti tool and analysis of learning device documents. The findings show that religious education requires a holistic learning approach from teachers to guide students' moral formation with skill reinforcement, holistic assessment, appropriate rubrics, and also an approach tailored to the variations in topography and the role of parents as a cultural asset of students' families, contributing to students' academic achievement.